2012
DOI: 10.1104/pp.112.198473
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Physiological Function of the Wax Layers Coating Arabidopsis Leaves: β-Amyrin Negatively Affects the Intracuticular Water Barrier    

Abstract: Plants prevent dehydration by coating their aerial, primary organs with waxes. Wax compositions frequently differ between species, organs, and developmental stages, probably to balance limiting nonstomatal water loss with various other ecophysiological roles of surface waxes. To establish structure-function relationships, we quantified the composition and transpiration barrier properties of the gl1 mutant leaf waxes of Arabidopsis (Arabidopsis thaliana) to the necessary spatial resolution. The waxes coating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 47 publications
3
94
0
2
Order By: Relevance
“…This coating material may prevent water loss during transpiration. Wax material is insoluble in ether leading to a higher crude fat contained in forage material (Buschhaus & Jetter, 2012). The general result showed that EE increased with the increased generative stage.…”
Section: Discussionmentioning
confidence: 51%
“…This coating material may prevent water loss during transpiration. Wax material is insoluble in ether leading to a higher crude fat contained in forage material (Buschhaus & Jetter, 2012). The general result showed that EE increased with the increased generative stage.…”
Section: Discussionmentioning
confidence: 51%
“…A detailed quantitative chemical analysis of leaf wax and a corresponding functional analysis of the water barrier properties of the cuticles of the Arabidopsis glabra1 (gl1) (At3g27920) mutant were recently performed (Buschhaus and Jetter, 2012). This study demonstrated that the upper (adaxial) and lower (abaxial) leaf surfaces differed in their wax loads and had distinct wax compositions.…”
Section: Specific Cuticular Wax Fractionsmentioning
confidence: 99%
“…Specific compound classes appear to be associated with water barrier properties of the cuticle; notably, the more nonpolar components, such as alkanes, tend to be associated with decreased CWP, while nonaliphatic wax compounds, such as triterpenoids, are likely a less effective water barrier (Leide et al, 2007;Buschhaus and Jetter, 2012). This is consistent with a model in which cuticular waxes localize within either crystalline or amorphous domains of the cuticle, with aliphatic compounds forming crystallite "rafts" that are impervious to water, forcing water, and other polar metabolites, to diffuse by a circuitous route through the amorphous domains that are formed by more polar and cyclic waxes (Riederer and Schreiber, 1995).…”
Section: Cuticle Structure and Water Barrier Propertiesmentioning
confidence: 99%